Strategi Inovatif dalam Mengelola Risiko Pasokan Bahan Baku Limbah Plastik - Ikhbar, Samsul; Yulianti, Rahmah; Maksalmina, Maksalmina; Ulfia, Ulfia; Malisi, Syibran (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
This research discusses innovative strategies for managing supply risks of plastic waste materials for SMEs and startups in the recycling sector. Stable and high-quality raw material availability is crucial for maintaining production efficiency, profitability, and environmental sustainability. However, challenges such as fluctuating supply volumes, inconsistent waste quality, and low community participation remain major obstacles. Using a conceptual approach, this paper explores three main strategies to mitigate these risks: supply source diversification, supply chain digitalization, and collaboration with external actors. Digitalization through IoT, big data, and blockchain technologies enhances transparency and efficiency in supply management. Meanwhile, partnerships with governments, communities, waste banks, and financial institutions strengthen supply chain sustainability through regulatory, financial, and social innovation support. Additionally, incentive mechanisms such as deposit-refund systems and eco-point reward programs effectively increase community participation in waste collection. The findings indicate that the synergy between technological innovation, multi-sector collaboration, and public policy forms the core foundation for developing a resilient, inclusive, and sustainable plastic waste supply chain.